2011
DOI: 10.1111/j.1476-5381.2010.01133.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the molecular interactions of two antagonists, MEN16132 or icatibant, at the human kinin B2 receptor

Abstract: BACKGROUND AND PURPOSEIcatibant is a well-known kinin B2 receptor antagonist currently used for angiooedema attacks. MEN16132 is a non-peptide B2 receptor antagonist, more potent and long lasting than icatibant in different models. Here we studied the reasons for these differences between the two antagonists. EXPERIMENTAL APPROACHRate of reversibility (over about 3 h) of the functional receptor blockade exerted by the antagonists was compared (inositol phosphates accumulation assay) in CHO cells expressing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 39 publications
2
19
0
Order By: Relevance
“…Moreover, this idea also explains the observed effect of the mutation Asn 297 Ala in close contact with Trp 256 [39]. Unfortunately there are no results available on the mutation of Ile 110 or Phe 259 on the affinity of the ligand, but according to the present modeling study it is expected one order of magnitude decrease as shown in fasitibant [31]. On the other side of the molecule anatibant and fasitibant exhibit differential stereochemical features that force them to bind in a differential way.…”
Section: Anatibantsupporting
confidence: 58%
See 2 more Smart Citations
“…Moreover, this idea also explains the observed effect of the mutation Asn 297 Ala in close contact with Trp 256 [39]. Unfortunately there are no results available on the mutation of Ile 110 or Phe 259 on the affinity of the ligand, but according to the present modeling study it is expected one order of magnitude decrease as shown in fasitibant [31]. On the other side of the molecule anatibant and fasitibant exhibit differential stereochemical features that force them to bind in a differential way.…”
Section: Anatibantsupporting
confidence: 58%
“…The final complex considered for refinement was selected based on the degree of fulfilment of diverse site-directed mutagenesis studies. Special attention was given to residues Trp 86 , Ile 110 , Trp 256 , Asp 266 and Tyr 295 [31].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fasitibant (MEN16132) (1, in Figure 1) is a potent antagonist of the BK B2 receptor with a Ki of 0.09 nM [31]. The structure of fasitibant bound to the model receptor from the present docking study is shown in Figure 5.…”
Section: Fasitibantmentioning
confidence: 99%
“…The choice of this ligand was due to the abundant information available from site directed mutagenesis experiments [31]. Finally, the ligand-receptor complex was embedded in a lipid bilayer and refined using molecular dynamics.…”
Section: Methodsmentioning
confidence: 99%